Olhares acerca do programa condominio amigo: uma proposta de intervenção - Ferreira, Ana Teresa Ramos (2013)
Friendly Condominium Program viewings as an intervention proposition. We have as a main goal to elaborate considerations about the intervention proposition in the Friendly Condominium Program in relation to the getting old process and the elderly support. Concerning the applied methodology, the research has a qualitative aspect which methodologic proposion was developed through a combination of a bibliographic, documental and field research in which the taking part in the observation process was applied. Therefore, we take the contributions of many aging and urbanization authors as basis to this research. The material collected to be analysed was the result of the written report of the three qualifying course and other written materials belonging to the OLHE Program in the years of 2009 and 2010. As well as, the attendance and observation in the last course which happened in the Copan building, in the year 2010, and the everyday sociability and reports, which intention was to illustrate the aspects referring to the intervention proposition in the Friendly Condominium. We come to the conclusion that the qualifying program purpose is obtained. The four meetings of two hours each and the themes studied are suitable with the proposed goal and they also make people reflect based on the informations, as well as, make people arouse interest to the necessity of a supporting and solidarity group organization. Nevertheless, this goal will only be reached if everybody takes place in the process (the building employees, elderly, tenants and works manager). We believe that the goals will only be reached based on a thinking way change through an information education program about the aging and the solidarity groups